Emfisema Subkutis Derajat 5 pada Pasien Rekuren Pneumotoraks Spontan Sekunder : Sebuah Laporan Kasus - Dwikarlina, Intan; Wijaya, Rendy; Antariksa, Genta; Sari, Fitri; Putra, Christian; Sarti, Fitri (Jurnal Klinik dan Riset Kesehatan, 2023)
Background: Subcutaneous emphysema is a condition where persistent air exists in the subcutaneous layer of the skin. Subcutaneous emphysema occurs through various etiologies, one of which is due to the rupture of the alveoli that cause air infiltration between the connective tissues in patients with spontaneous pneumothorax. Case Presentation: A 53-year-old man complained of shortness of breath that appeared suddenly after the patient defecated. Complaints of chest tightness accompanied by extensive swelling throughout the body starting from the patient’s genital to the entire patient's face. The patient had a history of secondary spontaneous pneumothorax and a history of suffering from tuberculosis recurrence in 2021. Discussion: Subcutaneous emphysema occurs when air enters the tissues under the skin and soft tissues. Subcutaneous emphysema can be classified into five grades based on its severity. In this case report, grade 5 subcutaneous emphysema occurred because of a patient's right lung history of pneumothorax. Pneumothorax can be traumatic or spontaneous. Spontaneous pneumothorax can be divided into primary (without a clear cause) or secondary (associated with lung disease). The patient also has a history of tuberculosis and post-tuberculosis obstructive syndrome (SOPT). Patient management includes chest tube placement, oxygen therapy, and subcutaneous air decompression measures. Conclusion: In this case report, a grade 5 subcutaneous emphysema with a history of tuberculosis infection responded well to chest tube insertion as illustrated by the gradual reduction in emphysema degrees. Medical personnel is needed to carry out a holistic and comprehensive history and medical examination regarding the risk factors for grade 5 subcutaneous emphysema.